Neonatal Hyperthyroidism and Long-acting Thyroid Stimulator Protector. Issue 5946 (21st December 1974) - Nutt, J.; Clark, F.; Welch, R. G.; Hall, R.
Abstract : Neonatal hyperthyroidism has been thought to result from transplacental passage of long-acting thyroid stimulator (L.A.T.S.) from a mother with Graves's disease. A case is presented here in which no L.A.T.S. was detected in the mother or neonate but another immunoglobulin, L.A.T.S. protector, a specific human thyroid stimulator, was shown to be present in the mother's serum. This stimulator may have been the cause of the neonatal hyperthyroidism.